TI_GERICHTE 15.2021.141 vom 14. Februar 2022 , Ricorso contro il pignoramento di reddito. Ordine legale di pignoramento - TI Tribunale d'appello (2022)
Ricorso contro il pignoramento di reddito. Ordine legale di pignoramento